First observation of Λ 0𝑏 → Σ([ast])𝑐⁢𝐷([ast])−𝐾− decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; et al. (Physical review, 2024)
The four decays, Λ0𝑏 →Σ(*)𝑐⁢𝐷(*)−⁢𝐾−, are observed for the first time using proton-proton collision data collected with the LHCb detector at a center-of-mass energy of 13 TeV, corresponding to an integrated luminosity of 6  fb−1. By considering the Λ0𝑏 →Λ+𝑐⁢¯𝐷0⁢𝐾− decay as reference channel, the following branching fraction ratios are measured to be ℬ⁡(Λ0𝑏→Σ𝑐⁢𝐷−⁢𝐾−)ℬ⁡(Λ0𝑏→Λ+𝑐⁢¯𝐷0⁢𝐾−)=0.282±0.016±0.016±.005,ℬ⁡(Λ0𝑏→Σ*𝑐⁢𝐷−⁢𝐾−)ℬ⁡(Λ0𝑏→Σ𝑐⁢𝐷−⁢𝐾−)=0.460±0.052±0.028,ℬ⁡(Λ0𝑏→Σ𝑐⁢𝐷*−⁢𝐾−)ℬ⁡(Λ0𝑏→Σ𝑐⁢𝐷−⁢𝐾−)=2.261±0.202±0.129±0.046,ℬ⁡(Λ0𝑏→Σ*++𝑐⁢𝐷*−⁢𝐾−)ℬ⁡(Λ0𝑏→Σ++𝑐⁢𝐷−⁢𝐾−)=0.896±0.137±0.066±0.018, where the first uncertainties are statistical, the second are systematic, and the third are due to uncertainties in the branching fractions of intermediate particle decays. These initial observations mark the beginning of pentaquark searches in these modes, with more datasets to become available following the LHCb upgrade.
Gesehen am 30.06.2025
Veröffentlicht: 22. August 2024
*LHCb Collaboration: R. Aaij, S. Bachmann, L. Carus, R. Caspary, S. Celani, C. Cocha Toapaxi, M. De Cian, L. Dittmann, S. Esen, G. Frau, P.A. Günther, X. Han, S. Hansmann-Menzemer, P. Herrero Gascon, J. Hu, C. Langenbruch, B. Leverington, J. Marks, M.P. Morgenthaler, P.R. Pais, S.R. Roy, M. Ruiz Diaz, G. Tuci, L.H. Uecker, D.J. Unverzagt, U. Uwer, C. Wang, L. Witola, Y. Zhao, A. Zhelezov [und 1061 weitere Personen]
Im Titel sind die Zahl 0, [ast] sowie die Plus- und Minus-Zeichen hochgestellt und die Buchstaben b und c tiefgestellt
Im Titel ist [ast] als Tropfensternchen dargestellt